A 5V 124MW 64 – Bit Advanced Comparator for DSP Processor - Thota Mounika (Advanced Aspects of Engineering Research Vol. 5, 2021)
A 5V, 124mw 64-bit Advanced Comparator for DSP Processor is proposed in this paper. This paper briefly presents comparison of the modified and existing 64 - bit binary comparator designs, which allows reducing power consumption and delay. Some modifications have done in existing 64- bit binary comparator design to improve the performance of the circuit. Comparison between modified and existing 64 – bit binary comparator designs is calculated by simulation that is performed in Tanner EDA Tool.